2019
DOI: 10.4336/2019.pfb.39e201801713
|View full text |Cite
|
Sign up to set email alerts
|

Coroamento com papelão para controle de braquiária na formação de povoamento para restauração florestal

Abstract: A presença de plantas daninhas em povoamentos visando restauração florestal pode ocasionar prejuízos, pois podem comprometer o crescimento de espécies arbóreas. Objetivou-se avaliar a eficácia do coroamento com papelão no controle de Urochloa spp. em área de restauração florestal. Avaliou-se a sobrevivência e crescimento de oito espécies arbóreas nativas e os custos de manutenção de coroamento manual (T1) e coroamento com papelão (T2). Constatou-se que, aos nove meses após o plantio das mudas e colocação do pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…However, in all those studies the weeds were crowned with hoe before placing the cardboard, which involves additional labor costs. The importance of controlling grasses in reforestation projects aims to obtain greater growth and survival gains for tree species (Ammondt & Litton, 2012;Dias et al, 2016;Santos et al, 2019). Gonçalves et al (2018) demonstrated that manual crowning of seedlings can be replaced by crowning with cardboard without hindering growth and with the benefit of reducing seedling mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in all those studies the weeds were crowned with hoe before placing the cardboard, which involves additional labor costs. The importance of controlling grasses in reforestation projects aims to obtain greater growth and survival gains for tree species (Ammondt & Litton, 2012;Dias et al, 2016;Santos et al, 2019). Gonçalves et al (2018) demonstrated that manual crowning of seedlings can be replaced by crowning with cardboard without hindering growth and with the benefit of reducing seedling mortality.…”
Section: Resultsmentioning
confidence: 99%
“…One of the greatest benefits of crowning seedlings with cardboard can be related to the lower cost of operation compared to traditional manual crowning, although the quality of the cardboard and the volume of rainfall in the area can increase these costs (Dias et al, 2019). In a study carried out in a riparian forest in the Atlantic Forest biome, the use of cardboard cut the working time in half (Palhares, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a criação de novas tecnologias tem sido uma prioridade nas pesquisas de restauração. Por exemplo, o disco ou placa de papelão, que é um dispositivo usado no coroamento de mudas, pode reduzir a incidência da matocompetição nos primeiros anos de plantio, além de substituir o coroamento convencional que pode demandar maior investimento de recursos (Dias et al, 2019). Por outro lado, a manta geotêxtil tem sido usada como alternativa para reduzir o nível de infestação de plantas daninhas e sua influência negativa sobre a sobrevivência e crescimento das espécies arbóreas plantadas ou provenientes da regeneração natural (Polster, 2002;Artioli & Correa, 2019).…”
Section: Introductionunclassified